2020
DOI: 10.1101/2020.08.06.239772
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuous constant pH Molecular Dynamics Simulations of Transmembrane Proteins

Abstract: Many membrane channels, transporters, and receptors utilize a pH gradient or proton coupling to drive functionally relevant conformational transitions. Conventional molecular dynamics simulations employ fixed protonation states, thus neglecting the coupling between protonation and conformational equilibria. Here we describe the membrane-enabled hybrid-solvent continuous constant pH molecular dynamics method for capturing atomic details of proton-coupled conformational dynamics of transmembrane proteins. Exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…The membrane-enabled hybrid-solvent CpHMD method 22,23 has been validated for pK a calculations and pH-dependent simulations of transmembrane proteins 23,25,26 . The detailed protocols can be found here 24 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The membrane-enabled hybrid-solvent CpHMD method 22,23 has been validated for pK a calculations and pH-dependent simulations of transmembrane proteins 23,25,26 . The detailed protocols can be found here 24 .…”
Section: Methodsmentioning
confidence: 99%
“…Towards understanding the molecular mechanism of mOR activation by fentanyl, here we elucidate the detailed fentanyl-mOR binding mechanism by exploiting a morphinanbound mOR crystal structure and several molecular dynamics (MD) methods, including the weighted ensemble (WE) approach [19][20][21] for enhanced path sampling and membraneenabled continuous constant-pH MD (CpHMD) with replicaexchange [22][23][24] . The latter method has been previously applied to calculate pK a s and describe proton-coupled conformational dynamics of membrane channels 25 and transporters 23,26,27 .…”
mentioning
confidence: 99%
“…Towards understanding the molecular mechanism of mOR activation by fentanyl, here we elucidate the detailed fentanyl-mOR binding mechanism by exploiting a morphinan-bound mOR crystal structure and several state-of-the-art molecular dynamics (MD) methods, including the weighted ensemble (WE) approach 1921 for enhanced path sampling and membrane-enabled continuous constant-pH MD (CpHMD) with replica-exchange. 2224 The latter method has been previously applied to calculate p K a ’s and describe protoncoupled conformational dynamics of membrane channels 25 and transporters. 23,26,27 Surprisingly, WE path sampling found that when His297 adopts the HID tautomer, fentanyl can move deeper into the mOR and establish an alternative binding mode through hydrogen bonding with His297.…”
Section: Introductionmentioning
confidence: 99%
“…This category includes the use of all-atom, constant-pH molecular dynamics (cpHMD) simulations and quantum mechanical (QM) methods. In cpHMD, virtual titrations of multiple protein side chains are performed simultaneously. This method, like free energy perturbation (FEP) and thermodynamic integration (TI), uses a λ-coupling constant to alchemically drive changes in protonation states. However, in cpHMD, λ is influenced by the environmental energetics.…”
Section: Methodsmentioning
confidence: 99%